Case Report: Positive Outcome of a Suspected Drug-Associated (Immune Mediated) Reaction in a 4-Year-Old Male French Bulldog - Lecru, Line-Alice; Combarros, Daniel; Castilla-Castaño, Eloy; Delverdier, Maxence; Cadiergues, Marie-Christine; Pressanti, Charline (Frontiers in Veterinary Science, 2021)
Toxic epidermal necrolysis (TEN) is a rare and severe life-threatening syndrome characterized by apoptosis of keratinocytes resulting in devitalization of the epidermis affecting more than 30% of skin surface. In humans and animals, this condition is mostly triggered by drugs. Identification of the putative agent and its withdrawal are crucial to successful management of a patient with TEN. In this case study, we report the clinical features, histopathological findings and management of a dog with TEN. A 4-year-old intact male French bulldog presented with acute onset of severe lethargy and cutaneous ulcerations on the footpads, scrotum, and hind limbs associated with marked pain. A Stevens-Johnson syndrome/ TEN was suspected and drugs, especially beta-lactams, were withdrawn. Histopathology confirmed the diagnosis of epidermal necrosis. Advanced supportive therapy, pain management and skin care led to rapid remission. Early identification and removal of the suspected medication was crucial to improving TEN prognosis in this dog. Antibiotics (penicillin, ampicillin, cephalexin and sulfonamides) are frequently involved in adverse cutaneous reactions in dogs. Ideal treatment remains elusive is humans and dogs and this disease has a poor prognosis. Supportive care combined with pain management and treatment of the cutaneous ulcerations is essential.